Effects of Calf Horn as Chews on the Behavior of Laboratory Dogs. Issue 1 (2nd January 2020) - Ketter, Daphne A.; Klima, André; Küchenhoff, Helmut; Dobenecker, Britta; Schmidt, Jörg; Erhard, Michael H.; Döring, Dorothea
ABSTRACT: It is increasingly required that non-human animals in laboratories are provided with adequate enrichment to promote the welfare of the animals. In a previous publication we showed that laboratory dogs intensively used the horn of calf hooves as chewing objects. In this report, we describe the effect of calf horn on selected behaviors of 62 laboratory dogs (60 beagles, two Foxhound crossbreds) in three research facilities (A, B, C). In addition, we assessed the dogs' tooth condition and fecal consistency. The selected behaviors: "aggressive behavior, " "mounting, " "tussle, " "coprophagy, " "manipulation" of the equipment and "abnormal behavior" did not change. In facilities A and C, the dogs receiving horn showed a significant reduction in staying near the fence of the kennel and observing the outside area. By analyzing the overall behavior in facility B, we found that "exploration" increased with horn, whereas "inactivity, " "social play" and "other social behavior" decreased. In conclusion, the results indicate that horn of calf hooves offers alternative stimulation. We found positive effects on tartar/plaque reduction and fecal consistency which should be confirmed in further studies.